Sustainability of supply chains in the wake of the coronavirus (COVID-19/SARS-CoV-2) pandemic: Lessons and trends - Ana Beatriz Lopes de Sousa Jabbour; Charbel José Chiappetta Jabbour; Martin Hingley; Eliseo Luis Vilalta-Perdomo; Gary Ramsden; David Twigg (Modern Supply Chain Research and Applications, 2020)
Purpose The purpose of this article is to address the prioritisation and focus of supply chain managers subsequent to coronavirus disease 2019 (COVID-19)/severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the great lockdown of 2020. Design/methodology/approach In this article, concepts and trends on resilient and sustainable supply chains are systematized. Main trends in sustainability of supply chains in the wake of COVID-19 are presented. Findings Guidelines on building smarter and more resilient supply chains are provided and future tendencies, which includes the increase of a sustainable consumption perspective, are highlighted. Originality/value This is a conceptual article blended with a practical approach aiming to propose guidelines for managers and scholars on how to address supply chain management challenges after the coronavirus pandemic.
Keywords: 650; Coronavirus; COVID-19; Resilience; Supply chain management; Sustainable consumption